Study of the Sustainability of Potato Farms in the Region of Oued Souf (Southern Algeria) - Djouhri Nesrine; Bouammar Boualem; Dadamoussa Mohamed Lakhdar (Turkish Journal of Agriculture: Food Science and Technology)
The objective of this study is to diagnose the potato sector in the El Oued region by highlighting the technical and environmental situation of this sector. For this purpose, a field survey was carried out at the level of 75 farms in the El Oued region. The Oued Souf region’s Farm Sustainability Indicator (IDEA) is important. The assessment of agro-ecological, socio-territorial and economic indicators indicates that the agro-ecological indicator is the most represented by (the indicator of fertilizer and agricultural practices) by 98 out of 100. The results of this study show that this crop presents a good adaptation to the conditions of the region. This sector is undergoing significant development and is of great importance because this agricultural activity represents an economic potential at the local, regional and national levels. However, this sector remains fragile in relation to various constraints of a technical nature (unreasonable irrigation and fertilization and high seed prices), economic (price fluctuations and disorganized markets) and environmental (diseases, weeds) which directly influence the functioning of farms and therefore their profitability. This is why it is necessary to face the problems encountered and fight against the factors that can hinder the sustainability of this sector and give a competitive value.